Slope stability estimation using a danger level approach for monitoring landslide prone areas - Siti Nurbaidzuri Reli,; Izham Mohamad Yusoff,; Muhamad Uznir Ujang, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Slope stability evaluation is an essential element in assessing landslide hazards and ensuring the safe design of structures and infrastructure. There has been increased awareness of the need to give greater attention to these phenomena. However, there is no general rule for classifying safety factors of the slope. The factor of safety (FOS) is used globally to determine slope stability by identifying shear strength and shear stress. However, the FOS cannot become the only assessment to evaluate slope stability. This research focuses more on the infiltration of soil-water that reduces the strength of slopes based on the danger level (DL). DL is divided into four categories: low, moderate, high, and very high. To estimate slope stability, four main locations are set on the slope: P1 (highest point), P2, P3 and P4 (lowest point). The DL value is determined using FOS, a rainfall threshold, soil-water infiltration, and soil classification. The DL value for P1 is 0.567 (moderate risk), while the DL values for P2, P3, and P4 are 0.116, 0.073, and 0.095 (very high risk), respectively, indicating that this slope is hazardous. Determining hazardous slope points will be easier, as DL has classified specific slope locations with exact risk values.